A slowly-growing solitary skip lymph nodule of occult gastric cancer above the neck of pancreas: a case report - Yuhao Tang; Xiaowei Sun; Li Xu (Surgical Case Reports)
Abstract Background Skip lymphatic metastasis (SK) is an exceptional and characteristic pattern of lymph node metastasis in gastric cancer (GC) with infrequent incidence. This is an extremely rare report of occult gastric cancer with solitary skip lymphatic metastasis as the initial and primary observation. Case presentation A 61-year-old woman, who complained of epigastric discomfort for several years, presented a solitary nodule upon pancreas neck examination by CT without performance on the primary lesion, even gastroscopy. During the preoperative 4-month follow-up, the nodule stayed stable without any therapy. The postoperative pathological examination confirmed the consistent diagnosis of gastric adenocarcinoma between the nodule and the stomach lesion, which was found by preoperative random biopsy of the mucosa. Conclusions This case highlights the concentration on vigilance to the SK of GC and a closer observation for intra-abdominal nodules, even radiological suspicion of a benign lesion.